Integrasi Evaluasi Eksperimental dan Analisis Bibliometrik Photosynthetic Bacteria dan Jakaba sebagai Bioaktivator Pertanian Organik - Nanda; Rafiqah Amanda Lubis; Mukhlis; Fery Endang Nasution; Luky Wahyu Sipahutar (Postgraduate, University of Mataram, 2025)
The excessive use of synthetic chemical inputs in agriculture has led to soil degradation, highlighting the need for environmentally friendly bioactivator alternatives. This study aims to integrate bibliometric analysis and experimental evaluation of Photosynthetic Bacteria (PSB) and Jakaba (Corallomycetella repens) as bioactivators in organic farming systems. Bibliometric analysis was conducted using Scopus publications from 2015–2025 and visualized with VOSviewer to map research trends, dominant keywords, and the publication status of PSB and Jakaba. A field experiment was then carried out in Kaluku Tinggu Village, Sigi District, using hybrid corn (Bisi-18) with four treatments: control, PSB, Jakaba, and a combination of PSB+Jakaba. Data were analyzed using ANOVA and Tukey HSD test, supported by Response Surface Methodology (RSM) for treatment effectiveness evaluation. Results showed that the PSB+Jakaba combination increased plant height (15.3%), fresh weight (20.9%), dry weight (25.1%), soil pH (13.5%), organic C content (41.2%), cation exchange capacity (27.6%), microbial population (24%), and dehydrogenase activity (36.3%) compared to the control. Active compounds such as IAA and siderophores from PSB, along with lignocellulolytic enzymes from Jakaba, played key roles in improving soil quality. This study bridges the scientific knowledge gap and reinforces the potential of local bioactivator formulations for sustainable organic farming on marginal land.